Singular phase nanophotonic cavities for heavy metal ion sensing - Rao, Anirudha Raghothama (Nanyang Technological University, 2021)
Optical sensors have shown great potential in providing label-free sensing solutions, which can analyze biomolecule binding through suitably functionalized surfaces on the sensing layer. Among optical sensors, phase-sensitive techniques show superior sensitivity compared to traditional sensing techniques due to the presence of a singular behavior in phase at the point of darkness. Very small changes in the refractive index on the device surface translates to an amplified difference in ellipsometer parameters and allow detection of concentrations down to the femtomolar regime. Here, we aim to obtain singular phase in a lithography-free nanophotonic cavity and exploit the extreme phase change for the detection of heavy metal ions at ultra-low concentrations. Heavy-metal ion pollution is a major issue in environmental contamination and for human health. Therefore, the detection of these ions at low concentrations is crucial for biomedicine and food safety applications. The concept of ultra-sensitive detection for heavy metals is demonstrated on Zinc ions at low concentrations using a nanophotonic cavity based sensor functionalized with PLGA.